Sally and… Cozmo? Training theory of mind using a toy robot: a pilot study - Ghiglino, Davide; Floris, Federica; De Tommaso, Davide; Wykowska, Agnieszka (Frontiers in Psychology, 2025)
IntroductionChildren with autism spectrum disorder (ASD) often show impairments in Theory of Mind (ToM). This pilot study examined whether a commercially available toy robot (Cozmo) could support false-belief training within an Applied Behavior Analysis (ABA) framework.MethodsFourteen children with ASD completed a two-period crossover design comparing robot-assisted training with standard therapy. Sessions used adapted false-belief tasks (Deceptive Box, Sally-Anne) delivered through therapist-controlled interactions with Cozmo. ToM and emotion recognition were assessed with NEPSY-II at T0, T1, and T2.ResultsRobot-assisted sessions produced greater improvements than standard therapy alone on both NEPSY-II Emotion Recognition and ToM subscales, as confirmed by mixed-effects models.DiscussionFindings suggest that an affordable toy-like robot can be feasibly integrated into structured clinical interventions and may enhance ToM-related outcomes in children with ASD, warranting further evaluation in larger samples.